Pregnancy and Hymenoptera venom allergy. Issue 5 (October 2020) - Bonadonna, Patrizia; Mauro, Marina; Preziosi, Donatella; Pravettoni, Valerio
Abstract : Purpose of review: To evaluate the indication to perform venom immunotherapy (VIT) during pregnancy considering the risks of adverse events during the build-up phase or the maintenance phase and analyzing specific articles and guidelines on VIT. Recent findings: Only few studies treat this argument and literature only counts one recent study on the topic, whereas recent guidelines state the behavior to keep in pregnancy. Summary: Hymenoptera venom allergy (HVA) affects about 7.5% of the European population. VIT is the only effective disease-modifying treatment for patients presenting anaphylactic reactions. VIT counts several mechanisms of action, with the increase of IgG1 and IgG4 and a cytokine impairment inducing a Th2–Th1 shift. Pregnancy is a health condition where a Th2 profile is required to prevent fetal rejection, so VIT could be a problem for the fetus when started during pregnancy.